2020
DOI: 10.1016/j.jclinepi.2020.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Social media can have an impact on how we manage and investigate the COVID-19 pandemic

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(140 citation statements)
references
References 21 publications
2
117
0
5
Order By: Relevance
“… 23 Short videos suggesting alternatives when the usual physical/psychological treatments are not feasible could also be beneficial, and social media were suggested as useful dissemination tools in that regard. 18 , 46 …”
Section: Discussionmentioning
confidence: 99%
“… 23 Short videos suggesting alternatives when the usual physical/psychological treatments are not feasible could also be beneficial, and social media were suggested as useful dissemination tools in that regard. 18 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…The 2009 H1N1 pandemic revealed that communication dynamics are vital for crisis management, and the use of practical tools for the transmission of health recommendations increases compliance [30]. Social media and online resources are now used by more than 3.8 billion, Twitter, and other social media channels can be a reliable source of health-related information [31]. The COVID-19 pandemic has demonstrated that emergency surgical teams and healthcare bodies could use online tools to disseminate guidelines and maintain communication in times of uncertainty [32].…”
Section: Discussionmentioning
confidence: 99%
“…A final word as to methodology. Even before Coronavirus limited the possibility of more traditional face-to-face research, social media platforms such as Facebook and Twitter, and online digital platforms such as Facebook messenger have been recognised for their unique value to health research and knowledge translation (14, 22). The value of this online forum was even more pronounced because of the novelty of the condition under examination.…”
Section: Discussionmentioning
confidence: 99%